Farmer's survey and field management of Chinese citrus fly(Bactrocera minax Enderlein) in Sweet orange orchards of Sindhuli, Nepal. - Gautam, Elina. (Tufts University. Tisch Library., 2020)
This objective of the poster was to find out the extent of damage of Bactrocera minax and its management practices adopted by farmers in sweet orange of Sindhuli district.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy